BREACH OF THE EUROPEAN UNION LAW ON ENVIRONMENTAL PROTECTION - Bugarski, Tatjana; Tubic, Bojan; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Within the European Union, as a regional international organization, environmental protection has been recognized as one of the significant objectives of action, which is achieved through the adoption of a large number of regulations. Sources of EU law on environmental protection are adopted in the form of directives, which Member States are obliged to adequately transfer to their national legislation and implement, effectively and timely, by adopting and implementing appropriate measures. In case of failure of Member States to comply with the above duties, the role of the European Commission and the Court of Justice of the European Union is of great importance. The paper presents randomly selected examples of the activities of the aforementioned bodies of the European Union in order to show the seriousness with which the application of EU law on environmental protection in member states is monitored.